ToyBox Study Malaysia: Improving healthy energy balance and obesity‐related behaviours among pre‐schoolers in Malaysia. Issue 3 (10th August 2018) - Reeves, S.; Poh, B. K.; Essau, C.; Summerbell, C.; Cheah, W. L.; Koh, D.; Lee, J. A. C.; Ruzita, A. T.; Gibson, E. L.
Abstract: The prevalence of childhood overweight and obesity is increasing in Malaysia and currently nearly 10% of children aged between 6 months and 12 years are overweight and almost 12% are obese. Early interventions to prevent excess weight gain are needed. ToyBox Study Malaysia is a feasibility project, funded by the Medical Research Council Newton‐Ungku Omar Fund, to assess the practicalities of adapting the existing European ToyBox Study intervention programme to the Malaysian kindergarten setting. The main aims of all ToyBox programmes are related to improving four key energy balance‐related behaviours, namely drinking water, eating healthy snacks and meals, reducing sedentary behaviour and increasing physical activity. Using stratified sampling, the ToyBox Study Malaysia intervention will be delivered and compared to usual practice by assessing behaviour, physical activity and health‐related outcomes as measured by questionnaires, accelerometry and anthropometry. It is hoped that the evidence‐based ToyBox Study Malaysia will help to achieve healthier energy balance‐related behaviours in the children and their families and provide lifelong benefits to health. This article provides information on the dietary patterns, physical activity levels and prevalence of overweight and obesity in Malaysian children, and the approach of the ToyBox Study Malaysia .